Eklavya Model Residential Schools in Odisha: An Evaluation - Padhi, Sambit Kumar (INDIAN EDUCATIONAL REVIEW, 2016)
It has been universally accepted that education is the basic input for sustainable development of people and nation. Realising the importance of education the State and Central Government have given wide attention for promotion of education among all categories in general and, socially and culturally disadvantaged groups in particular. The schedule tribes’ constitute the most backward among the weaker and disadvantaged sections in India. And only education can bring a visible change in their present life style. Many special schemes have been formulated in order to attract tribal children to school. However, review clearly underlines that they are far behind from the mainstream of life. For the upliftment of tribal people living in backward areas, Ministry of Tribal Affairs has launched a new concept of educational development– ‘Establishment of Eklavya Model Residential School (EMRS)’ in the country during 1997–1998. In Odisha, Eklavya Model Tribal residential school project was launched in the year 2000–2001. Over the periods of 12 years, 13 such EMRs have been established across the State covering total of 11 districts. The main aim of the study was to ascertain the effectiveness of the scheme; data were collected from the areas like — admission procedure for students, location and infrastructure, teaching and learning, assessment procedure etc.